Recent Advances in Microbiology 2011
DOI: 10.1201/b12222-7
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as an Antiviral Against Polyomavirus

Abstract: Background: To compare the effectiveness of liposomal tobramycin or polymyxin B against Pseudomonas aeruginosa in the Cystic Fibrosis (CF) sputum and its inhibition by common polyanionic components such as DNA, F-actin, lipopolysaccharides (LPS), and lipoteichoic acid (LTA).Methodology: Liposomal formulations were prepared from a mixture of 1,2-Dimyristoyl-sn-Glycero-3-Phosphocholine (DMPC) or 1,2-Dipalmitoyl-sn-Glycero-3-Phosphocholine (DPPC) and Cholesterol (Chol), respectively. Stability of the formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…The liposome encapsulated antibiotics demonstrated a significant increase in antimicrobial activity towards P. aeruginosa bacteria in the presence of DNA, F-actin, lipopolysaccharides and lipoteichoic acid. [44] It is worth noting that co-encapsulation of other antimicrobial substances together with an antibiotic into liposomes could improve the antimicrobial efficacy. Omri and coworkers showed that the co-encapsulation of gallium or bismuth-ethanedithiol with gentamycin or tobramycin in DPPC:Chol or DSPC:Chol, respectively, can increase the vulnerability of the bacterial cells and interfere with the expression of virulence factors, alginate, quorum sensing molecules and biofilm formation compared to the free antibiotic or the free antibiotic and the free metal combined.…”
Section: Protection Of the Antimicrobial Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…The liposome encapsulated antibiotics demonstrated a significant increase in antimicrobial activity towards P. aeruginosa bacteria in the presence of DNA, F-actin, lipopolysaccharides and lipoteichoic acid. [44] It is worth noting that co-encapsulation of other antimicrobial substances together with an antibiotic into liposomes could improve the antimicrobial efficacy. Omri and coworkers showed that the co-encapsulation of gallium or bismuth-ethanedithiol with gentamycin or tobramycin in DPPC:Chol or DSPC:Chol, respectively, can increase the vulnerability of the bacterial cells and interfere with the expression of virulence factors, alginate, quorum sensing molecules and biofilm formation compared to the free antibiotic or the free antibiotic and the free metal combined.…”
Section: Protection Of the Antimicrobial Agentmentioning
confidence: 99%
“…This can be attributed to the increase in viscoelasticity which limits the diffusion of the liposomes or a stabilization of the liposomes by the mucus which reduces the release of the antibiotic from the liposomes. [44] Alternatively, the liposomes might bind to alginate, preventing the nanocarrier to bind to the bacteria themselves or destabilizing the liposomes leading to premature release and subsequent inactivation of the antibiotic. [68] Although the addition of DNase and alginate lyase improved the activity of the free and liposomal antibiotics, no superiority of the liposomal formulation was observed.…”
Section: Absence Of Increased Anti-biofilm Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Encapsulation of these antibiotics in liposomes reduces formation of the electrostatic complex 100-fold, giving a 4-fold improved inhibition of P. aeruginosa colonies, suggesting a potential application in eradication of chronic lung infections associated with CF [184,187].…”
Section: Protective Vesicles Preventing Antimicrobial Degradationmentioning
confidence: 99%
“…CF sputum being rich in polyanionic components, namely mucin, DNA, F-actin, lipopolysaccharides and lipoteichoic acid has been shown to reduce the antimicrobial properties of the cationic antibiotics polymyxin and tobramycin, due to formation of an electrostatic-attraction complex, hampering complete eradication of the bacteria [99,187,188]. Encapsulation of these antibiotics in liposomes reduces formation of the electrostatic complex 100-fold, giving a 4-fold improved inhibition of P. aeruginosa colonies, suggesting a potential application in eradication of chronic lung infections associated with CF [184,187].…”
Section: Protective Vesicles Preventing Antimicrobial Degradationmentioning
confidence: 99%